Assessing benefits of innovative approaches addressing the pigeon pea and common bean productivity within maize-based cropping system and variable weather - Alliance of Bioversity International and CIAT (2021)
The dataset contains seven datasheets with different types of data i.e., cropping system physiological characteristics, radiation intercepting, gross margins, soil nutrient characterization, seasonal physical conditions of the soil, soil water infiltration and seasonal weather conditions. The data will be helpful in assessing how the different plant spacing patterns affects plant physiological and soil physical chemical characteristics under maize legume intercropping systems. The cropping system physiological characteristic datasheet contains data on maize leaf chlorophyll measurements using SPAD and soil moisture and temperature reading using time domain reflectometry. Radiation interception dataset contains data on photosythentically active radiation (PAR) fraction intercepted by plant canopy under different plant spacing arrangements. Besides is data on LAI under varying plant arrangements. Both reading were measured using AccuPAR LP-80 ceptometer during periods of limited cloud cover. Gross margin datasheet contains data on yields of the different plant (maize, beans and pigeon pea) components (grain, stover, maize toppings, haulms, stalks and husks). The different components were converted into gross revenue using the farm gate prices of each parameter. Besides, BNF data is also included to indicate the amount of N fixed from two experimental fields located in low altitude-low rainfall and medium altitude- low rainfall eco-zones. Soil nutrient characterization datasheet contains data on soil nutrient content at 0-20 cm depth which was sampled at block level during planting. Seasonal physical conditions of soil datasheet has data on daily soil physical conditions i.e., soil moisture, temperatures and bulk electrical conductivity during the cropping season. This data was measured at a meteorological station located in the low altitude-low rainfall eco-zone of Babati. Soil water infiltration data indicates the rate of water infiltrating under two suctions i.e., -2 cm sec2 and -6 cm sec2 using mini-disc infiltrometer at field level. Seasonal weather condition indicates daily weather data collected in three agro-ecological conditions of Babati during the 2019 long rain season.